Formulation and Evaluation of Avocado Leaf Extract (Persea americana Mill.) Cream Based on Variations Stearic Acid Concentration - Bahariyan Ramdhan; Anna L Yusuf (LPPM STIKes Muhammadiyah Ciamis, 2023)
Avocado leaves (Persea americana Mill.) contain flavonoid compounds as high as 8.11 mg, so they have potential in the acne healing process. The aim of this research is to create a formulation and evaluate an avocado leaf extract cream preparation. The method used is experimental. Avocado leaf extract cream preparations are made based on varying stearic acid concentrations of 5%, 10% and 15%. Evaluation of the preparation includes organoleptic tests, homogeneity tests, pH tests, spreadability tests, adhesion tests, and viscosity tests. Based on the organoleptic evaluation, the results showed that FI was slightly runny and contained bubbles, FII was slightly thick and FIII was thick. The FI color is brownish white, FII is yellowish white, and FIII is white, and all formulations have a characteristic creamy odor. The homogeneity test shows that all formulas have the same homogeneous preparation. The pH test of the cream preparation showed the same pH value, namely 6. The spreadability test resulted in good spreadability of the cream, namely between 5 and 6.8 cm. The cream adhesion test has an adhesion between 00.53 and 1.38 seconds. And finally, the viscosity test has a viscosity value between 4500 and 8900 mpa. According to the results of this research, avocado leaf extract cream can be used as a cream preparation, with the best stearic acid concentration being 15%.